2021
DOI: 10.1242/jeb.238790
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance and physiological regulation of essential trace metals in fish

Abstract: Trace metals such as iron, copper, zinc and manganese play essential roles in various biological processes in fish, including development, energy metabolism and immune response. At embryonic stages, fish obtain essential metals primarily from the yolk, whereas in later life stages (i.e. juvenile and adult), the gastrointestine and the gill are the major sites for the acquisition of trace metals. On a molecular level, the absorption of metals is thought to occur at least in part via specific metal ion transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 162 publications
0
7
0
Order By: Relevance
“…The results of the correlation analysis also revealed that some positive relationships exist between MMs in both brackish water and marine fish, indicating changes in the same direction (i.e., when a MM increases, other MMs also increase) [ 100 ]. Similarly, this may also reveal common absorption sites of MMs in both brackish and marine fish, their interaction, and possible source(s) of pollution [ 34 , 101 ]. Ali et al (2022) [ 102 ], also investigated toxic metals in commercial fishes from Bangladesh and found highly positive relationships between toxic metals, suggesting common sources and distribution patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the correlation analysis also revealed that some positive relationships exist between MMs in both brackish water and marine fish, indicating changes in the same direction (i.e., when a MM increases, other MMs also increase) [ 100 ]. Similarly, this may also reveal common absorption sites of MMs in both brackish and marine fish, their interaction, and possible source(s) of pollution [ 34 , 101 ]. Ali et al (2022) [ 102 ], also investigated toxic metals in commercial fishes from Bangladesh and found highly positive relationships between toxic metals, suggesting common sources and distribution patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Iron (Fe) has important roles in physiological processes such as oxygen transport, cellular respiration, and lipid oxidation reactions and is necessary for the normal function of the organs and tissues of fish (Chandrapalan and Kwong, 2021). Adding Fe-NPs to young carp and sturgeons' diets increased their growth rate to 30% and 24%, respectively (Rather et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the role of cytochrome P450 enzymes in the catalyzation of COC N-demethylation in fish liver has been investigated, shedding light on the metabolic pathways of COC in fish [ 149 ]. Additionally, lead and other trace elements have been shown to negatively affect endocrine function in fish, further emphasizing the potential for environmental contaminants to modulate the endocrine system in aquatic species [ 150 ].…”
Section: Bioaccumulation Of Illicit Drugs and Their Toxicitymentioning
confidence: 99%